2020
DOI: 10.1111/nph.16455
|View full text |Cite
|
Sign up to set email alerts
|

Structural evolution drives diversification of the large LRR‐RLK gene family

Abstract: Cells are continuously exposed to chemical signals that they must discriminate between and respond to appropriately. In embryophytes, the leucine-rich repeat receptor-like kinases (LRR-RLKs) are signal receptors critical in development and defense. LRR-RLKs have diversified to hundreds of genes in many plant genomes. Although intensively studied, a well-resolved LRR-RLK gene tree has remained elusive.To resolve the LRR-RLK gene tree, we developed an improved gene discovery method based on iterative hidden Mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
69
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(71 citation statements)
references
References 106 publications
2
69
0
Order By: Relevance
“…An additional twist when investigating potential peptide-receptor interactions is the presence of modified amino acid residues, in particular sulfated Tyr and hydroxylated Pro. We have confirmed that GSO and RGI homologues are present in non-flowering plants (Bowman et al, 2017;Liu et al, 2017;Man et al, 2020), and hypothesized that their respective ligands are conserved in the species where presumptive receptors are present. Using PHI-BLASTp, as described, we indeed retrieved ligand candidates from several species (Figure 1 and 5).…”
Section: Matching Dy Sulf Peptides With Receptorssupporting
confidence: 67%
“…An additional twist when investigating potential peptide-receptor interactions is the presence of modified amino acid residues, in particular sulfated Tyr and hydroxylated Pro. We have confirmed that GSO and RGI homologues are present in non-flowering plants (Bowman et al, 2017;Liu et al, 2017;Man et al, 2020), and hypothesized that their respective ligands are conserved in the species where presumptive receptors are present. Using PHI-BLASTp, as described, we indeed retrieved ligand candidates from several species (Figure 1 and 5).…”
Section: Matching Dy Sulf Peptides With Receptorssupporting
confidence: 67%
“…LRR RLKs form the major clade of membrane receptor proteins in plants and most contain an extracellular ligand binding domain, a membrane spanning domain and an intracellular kinase domain [ 46 , 62 , 63 , 64 , 65 , 66 , 67 ]. RLK is a large family with over 600 genes in Arabidopsis forming over 2% of the total protein [ 65 ].…”
Section: Moonlighting Kinasesmentioning
confidence: 99%
“…Plant RLKs form part of the monophyletic RLK and Pelle gene family sharing common ancestors with animal receptor kinases; in particular the kinase domain has similarities with Drosophila melanogaster Pelle kinase and interleukin 1 receptor associated kinases (IRAK) [ 46 , 65 , 68 ]. Diversity between the RLK and Pelle clades is massive amongst plants with rice for instance having more than twice the number of RLKs found in Arabidopsis [ 46 , 64 , 65 , 66 , 68 ], but quite limited in animals with four IRAK members in vertebrates [ 69 ]. This phenomenon is no doubt due to the need of plants to recognize and respond actively to environmental challenges.…”
Section: Moonlighting Kinasesmentioning
confidence: 99%
See 2 more Smart Citations